2018
DOI: 10.21577/0103-5053.20180125
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Acid Hydrolysis of Myricetin-3-O-rhamnoside Using Response Surface Methodology

Abstract: This study aimed to optimize the acid hydrolysis of glycosylated flavonols, to apply the optimum conditions for hydrolyzing Inga edulis extract (IEE), rich in glycosylated flavonols, and evaluating its impact on the antioxidant capacity. To evaluate the influence of three independent variables on the aglycone obtained after the reaction, the response surface methodology was applied using myricetin-3-O-rhamnoside (M3R) as a pure compound. The phenolic compound profile and antioxidant capacity were determined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Chemical synthesis of myricetin process can form myricetin as the final product by the steps such as hydrolysis, demethylation, methylation by using other constituents [ 52 , 97 , 103 ]. Tolosa et al reported an optimized acid hydrolysis of myricetin-3- O -rhamnoside to yield myricetin [ 111 ]. Table 1 shows content of myricetin and its glycosides in fruits, vegetables, and plant parts.…”
Section: Source Of Myricetinmentioning
confidence: 99%
“…Chemical synthesis of myricetin process can form myricetin as the final product by the steps such as hydrolysis, demethylation, methylation by using other constituents [ 52 , 97 , 103 ]. Tolosa et al reported an optimized acid hydrolysis of myricetin-3- O -rhamnoside to yield myricetin [ 111 ]. Table 1 shows content of myricetin and its glycosides in fruits, vegetables, and plant parts.…”
Section: Source Of Myricetinmentioning
confidence: 99%
“…Response surface methodology (RSM) was performed for process optimization. The empirical model of the optimum reaction parameters was calculated using suitable modeling techniques [23][24][25]. Figure 1 presents the XRD patterns of all four zeolites used as the catalyst in the ethanol conversion.…”
Section: Introductionmentioning
confidence: 99%